The lender of last resort concept: from Bagehot to the crisis of 2007 - Esther Jeffers (Revue de la Régulation)
The crisis that has unfolded since the summer of 2007 has provided an opportunity to experiment in vivo one of the most important pillars of economic theory: the lender of last resort (LOLR). We begin by examining the LOLR from a theoretical point of view, and describe its fundamental principles. We then try to understand the nature of the crisis, as well as how it was managed both from a European and an American LOLR perspective. We take up the main difficulties encountered by crisis management and try to draw the principal conclusions of what we have learned concerning actions taken by the lender of last resort in a globalized world.